The Jews of ancient Rome - Leon, Harry Joshua (Peabody, MA Hendrickson, 1995)
Includes bibliographical references and index.
First edition published Philadelphia, PA: Jewish Publication Society of America, 1960 (The Morris Loeb series).
Keywords: Jews -- Italy -- Rome -- History; Rome (Italy) -- Antiquities; Inscriptions, Jewish -- Italy -- Rome